2018
DOI: 10.1186/s12874-018-0546-2
|View full text |Cite
|
Sign up to set email alerts
|

How can we get Iraq- and Afghanistan-deployed US Veterans to participate in health-related research? Findings from a national focus group study

Abstract: BackgroundResearch participant recruitment is often fraught with obstacles. Poor response rates can reduce statistical power, threaten both internal and external validity, and increase study costs and duration. Military personnel are socialized to a specific set of laws, norms, traditions, and values; their willingness to participate in research may differ from civilians. The aims of this study were to better understand the views of United States (US) Veterans who served in Operation Enduring Freedom (OEF)/ Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
0
26
1
Order By: Relevance
“…Similarly, veterans in previous studies have indicated a general distrust with the VA healthcare system and add that vague language can fuel this distrust and is off-putting. 12,13 As such, the findings from this study regarding the use of the word lifestyle and the negative feelings it elicited among our participants caused us to consider alternate wording (i.e., holistic health promotion program) to provide a clear and more positive perception of RECLAIM to veterans.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, veterans in previous studies have indicated a general distrust with the VA healthcare system and add that vague language can fuel this distrust and is off-putting. 12,13 As such, the findings from this study regarding the use of the word lifestyle and the negative feelings it elicited among our participants caused us to consider alternate wording (i.e., holistic health promotion program) to provide a clear and more positive perception of RECLAIM to veterans.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, veterans in previous studies have indicated a general distrust with the VA healthcare system and add that vague language can fuel this distrust and is off-putting. 23,24 Therefore, it is important to consider alternate terminology to eliminate this as a potential barrier to participating in the RECLAIM program. As such, the ndings from this study regarding the use of the word lifestyle and the negative feelings it elicited among our participants forced us to consider alternate wording (i.e., holistic health promotion program) to provide a clear and more positive perception of RECLAIM to veterans.…”
Section: Discussionmentioning
confidence: 99%
“…While efforts have been made to prevent and reduce veteran suicide, the rate of suicide among post-9/11 veterans (ages [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] remains the highest of all veteran cohorts and has increased by 76% from 2005-2017, 6 indicating that more work is needed to effectively reduce the rate of suicide among this veteran cohort. Current suicide reduction and prevention strategies often narrowly focus on extreme psychopathology (e.g., post-traumatic stress disorder) and are frequently directed at veterans who have already indicated intent to harm.…”
Section: Introductionmentioning
confidence: 99%
“…The project design incorporated the findings of prior research indicating that military personnel might be reluctant to participate in research due to the sensitivity of the topics, lack of trust, and concerns regarding lack of anonymity and perceived risks to privacy (Littman, True, Ashmore, Wellens, and Smith, 2018). To reduce veteran concerns about privacy and address this community's reluctance to participate in recorded dialogue sessions, a field note template was developed to guide discussions and enable the CARM to take careful notes about what was said including direct quotes.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…This is particularly evident among the nation's 22 million US veterans. Despite a critical need for evidence-based approaches to service-related health issues, veterans are frequently reluctant to partner with or participate in the research enterprise (Bush, Sheppard, Fantell, & Bell, 2013;Braun, Kennedy, Sadler, & Dixon, 2015;Littman, True, Ashmore, Wellens, & Smith, 2018;Williams, Gatien, & Hagerty, 2012;Funderburk, Spinola, & Maisto, 2015). The purpose of this multi-state project was to invite veterans to dialogue about (1) their research priorities; (2) perceived barriers to research participation; (3) recommended strategies for engaging veterans in research; and (4) their preferences for receiving research findings.…”
Section: Introductionmentioning
confidence: 99%